Enhancing professional learning for rural educators by rethinking connectedness - Broadley, Tania (Society for the Provision of Education for Rural Australia, 2012)
Impending changes in Australian education brings forth the expected transformation of teachers working in schools. Three key points for transforming Australian schools has been identified by Gillard (2008a) including the improvement of quality teaching, ensuring every child benefits and mandating transparency and accountability. A number of initiatives were considered to assist with such reform including the implementation of a Digital Education Revolution, the move to the Australian Curriculum and the implementation of a National Framework for Professional Standards for Teaching. As these transformative initiatives are rolled out to teachers across Australia, the equitable access to PD to support all teachers, regardless of their geographical location, is in question. In line with the literature, the author proposes the concept of delivering PD and accessing PD from regional and remote areas be reconsidered. This research paper will outline the findings from the study including travel time being significant and impacting on teachers personal time; limited relief teachers impacting on access to PD; promotion and teacher registration being explicitly linked to PD; professional learning communities being valued but often limited by small staff numbers; professional learning conducted in the local context being preferred; professional learning established at the teacher and school level being desirable; teachers being confident in using technology and accessing PD online if required; and social cohesiveness being valued and often limited by isolation. Further this research has culminated in the development of a conceptual framework that would facilitate improving the amount and variety of professional learning available to regional and remote teachers.